Cane Toads on Cowpats: Commercial Livestock Production Facilitates Toad Invasion in Tropical Australia - González-Bernal, Edna; Greenlees, Matthew; Brown, Gregory P.; Shine, Richard (PLOS ONE, 2012)
Habitat disturbance and the spread of invasive organisms are major threats to biodiversity, but the interactions between these two factors remain poorly understood in many systems. Grazing activities may facilitate the spread of invasive cane toads (Rhinella marina) through tropical Australia by providing year-round access to otherwise-seasonal resources. We quantified the cane toad’s use of cowpats (feces piles) in the field, and conducted experimental trials to assess the potential role of cowpats as sources of prey, water, and warmth for toads. Our field surveys show that cane toads are found on or near cowpats more often than expected by chance. Field-enclosure experiments show that cowpats facilitate toad feeding by providing access to dung beetles. Cowpats also offer moist surfaces that can reduce dehydration rates of toads and are warmer than other nearby substrates. Livestock grazing is the primary form of land use over vast areas of Australia, and pastoral activities may have contributed substantially to the cane toad’s successful invasion of that continent.